(untitled) (Nepalese Journal of Radiology, 2023)
Introduction: Hepatocellular carcinoma (HCC) is the 3rd leading cause of cancer-related mortality. Ruptured HCC carries a high mortality if untreated. Peripherally located HCC has a higher risk of rupture. However, most of the ruptured HCCs on presentation are in an advanced stage and, hence are unresectable. Henceforth treatment options available are conservative and transcatheter embolization. Methods: Retrospectively, 8 patients with ruptured HCC who underwent trans arterial embolization were studied for hemostasis and 30-day mortality. Clinical history and laboratory data were obtained from the medical records of the patients, and radiological images were extracted from picture archiving and communication systems and studied. Results: The age ranged between 31 to 78 years and 7 were male. In patients presenting with sudden onset pain abdomen, ruptured HCC was suspected if there was a hemoperitoneum with or without extravasation of contrast adjacent to peripherally located HCC on CT angiography. Angiography revealed tumour blush with sentinel vessels in all. Two showed active contrast extravasation. Seven patients with relatively preserved liver function (Child A and B) attained both radiological and clinical hemostasis. One patient with Child C status died due to MODS on day 3 of embolisation. Three patients survived more than a year with additional liver-directed therapies. Two patients were lost to follow-up after discharge and two after six months. Conclusions: Transarterial embolization for ruptured HCC is an effective method of hemostasis and helps in achieving better survival by the additional benefit of tumor control and poor functional status of the liver predicts lower survival.